2001
DOI: 10.3354/meps221233
|View full text |Cite
|
Sign up to set email alerts
|

Inshore migration of the tropical eels Anguilla spp. recruiting to the Poigar River estuary on north Sulawesi Island

Abstract: To understand ecological and behavioral aspects of inshore migration of tropical eels, Anguilla spp., we collected 32 836 glass eels in the Poigar River estuary on north Sulawesi Island, Indonesia, in monthly collections from 1997 to 1999. The specimens were identified using morphological characters, and 3 species, A. celebesensis, A. marmorata, and A. bicolor pacifica, were found each year in fluctuating abundances. A. celebesensis was the most abundant species and comprised 73.5, 79.5, and 81.9% of all glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 26 publications
(41 reference statements)
2
64
0
2
Order By: Relevance
“…Various studies have examined the recruitment patterns of anguillid glass eels in both temperate and tropical regions (e.g. Sugeha et al 2001b;Sullivan et al 2006Sullivan et al , 2009. Less studied are the larvae of mesopelagic eels, which presumably metamorphose at a certain size and move into deeper water to start their juvenile stage, based on studies of the life histories of these eels (e.g.…”
Section: -3 Recruitment Behaviormentioning
confidence: 99%
“…Various studies have examined the recruitment patterns of anguillid glass eels in both temperate and tropical regions (e.g. Sugeha et al 2001b;Sullivan et al 2006Sullivan et al , 2009. Less studied are the larvae of mesopelagic eels, which presumably metamorphose at a certain size and move into deeper water to start their juvenile stage, based on studies of the life histories of these eels (e.g.…”
Section: -3 Recruitment Behaviormentioning
confidence: 99%
“…In Indonesia and the Philippines, A. marmorata recruitment peaks in February to March (Tabeta et al 1976, Budimawan 1997, Arai et al 2002, while in French Polynesia 2 annual peaks occur, 1 in January to February and 1 in March to April (Marquet 1992). In North Sulawesi, the Celebes Sea, recruitment peaks in January and May to June, preferentially at new moon (Sugeha et al 2001a). At Réunion Island (this study), fishermen collect glass eels together with goby-fry during the entire traditional fishing period from November to April.…”
Section: Recruitment Patternsmentioning
confidence: 99%
“…Recent studies specifically on A. japonica (Tzeng 2003) indicated that the otolith microstructure and microchemistry can provide some clues to understanding the early life history of fish during their migration from spawning grounds until recruitment, but little is known about the early life history of most tropical species, particularly A. marmorata (Sugeha et al 2001a;Arai et al 2002a, b;Miller et al 2002;Shiao et al 2003). Also, it was found that the age at metamorphosis from the leptocephalus to glass eel can be determined by changes in otolith microstructures and in strontium/calcium (Sr/Ca) ratios in daily growth increments (DGIs) of otoliths Tsai 1992, 1994;Tzeng 1995).…”
Section: Introductionmentioning
confidence: 99%